Legal innovative development of the region’s economy (Journal of actual problems of jurisprudence, 2018)
Scientific and technical potential of the main national wealth of any state. As the experience of most developed countries, the main way of economic development and prosperity – to be a leader in scientific and technical and innovative spheres. Innovation and innovation give resistance to economic decline, create conditions for active development of scientific and technological progress and improve the efficiency of the national economy and its competitiveness. Therefore, countries all over the world focus on the organization and effective management of innovation. The state in turn, using achievements of scientific and technological progress and innovation policy for the benefit of the citizens of your country implements a function aimed at improving the quality of life of the population. This article presents an overview of innovative activity and innovative potential of the regions of Kazakhstan. Also provides statistical data on innovative activity of regions. Considers the ways of improvement and formation of innovative policy of regions. Key words: innovation, region, innovative activity, innovative potential, innovative policy.